Information Technology Solutions for Healthcare - Zielinski, Krzysztof; Duplaga, Mariusz; Ingram, David (Health Informatics, 2006)
Understanding how healthcare is being transformed by IT is key to the improvement of medical standards and reduction of cost. The synergy between computer technology and medical services allows fascinating new possibilities for benefit in areas such as continuing care, chronic disease treatment and home monitoring, bringing with it the promise of essential changes in existing models of care delivery and system performance. This book presents the current and future trends in the transformation of healthcare services in the Information Society Era and is of great relevance to informatics professions, clinical managers and all clinicians using these new technologies as part of their practice. Information Technology Solutions for Healthcare addresses the priorities within international informatics and presents a thorough survey of the most promising e-health technologies, including internet-enhanced healthcare services and mobile technology via modern wireless technologies. It is illustrated with case reports identifying real applications of the techniques and focused on providing an integrated overview of e-health and medical, sociological and technical aspects of the application of e-health technologies.